Response‐guided telaprevir therapy in prior relapsers? The role of bridging data from treatment‐naïve and experienced subjects - Liu, Jiang; Jadhav, Pravin R.; Amur, Shashi; Fleischer, Russell; Hammerstrom, Thomas; Lewis, Linda; Naeger, Lisa; O'Rear, Jule; Pacanowski, Michael; Robertson, Sarah; Seo, Shirley; Soon, Greg; et al. (Hepatology (Baltimore, Md.), 2013)
The purpose of this report is to illustrate the US Food and Drug Administration's rationale for approving response‐guided therapy (RGT) for telaprevir (TVR) in combination with pegylated interferon‐α and ribavirin (P/R) for the treatment of adults with genotype 1 chronic hepatitis C who were prior relapsers. RGT was prospectively evaluated in two registration trials of treatment‐naïve subjects. In these studies, RGT allowed subjects who achieved undetectable hepatitis C virus RNA from weeks 4 and 12, known as extended rapid virologic response (eRVR), to stop all treatments at 24 weeks. A patient without eRVR received an additional 36 weeks of P/R after 12 weeks of a TVR triple regimen (total of 48 weeks). However, RGT in prior P/R relapsers was not prospectively evaluated. Empirical cross‐trial data indicated high sustained virologic response rates (>90%) in prior relapsers achieving eRVR, irrespective of P/R duration (24 or 48 weeks). Further analyses demonstrated that interferon responsiveness does not change in P/R‐experienced subjects with a second round of P/R. The comparability in interferon responsiveness across treatment courses allowed us to bridge data between treatment‐naïve and P/R‐experienced subjects to support the approval of RGT in prior relapse subjects. (HEPATOLOGY 2013)